Aerothermoelastic Load Calculation for Hypersonic Vehicles Based on Multiphysics Coupled Analysis. (18th September 2018) - Chen, Hao; Xu, Min; Qiu, Zihua; Xie, Dan; Wang, Yabin
Abstract : To fulfill the design objective of a structure and thermal protection system, accurate load environment prediction is very important, so we present a high-fidelity aerothermoelastic load calculation method based on a partitioned computational fluid dynamics/computational structural dynamics/computational thermal dynamics (CFD/CSD/CTD) coupling analysis. For the data transformation between the CFD/CSD/CTD systems, finite element interpolation (FEI) is explored, and a shape-preserving grid deformation strategy is achieved via radical basis functions (RBFs). Numerical results are presented for validation of the proposed CFD/CSD/CTD coupling analysis. First, a simply supported panel in hypersonic flow is investigated for results comparison of the proposed coupling method and previous work. Second, a hypersonic forebody is investigated to explore the aerothermoelastic effects while considering the feedback between deformation and aerodynamic heating. The results show that the CFD/CSD/CTD coupling method is accurate for analysis of aerothermoelasticity. In addition, considering the aerothermoelastic effect, the shear force and bending movement increase with time before 900 s and decrease after 900 s, and at 900 s increased percentages of 5.7% and 4.1% are observed, respectively. Therefore, it is necessary to adopt high-fidelity CFD/CSD/CTD coupling in the design of a structure and thermal protection system for hypersonic vehicles.